Reactulization of Islamization of Islamic Science and Knowledge in an Ontological-Historical Perspective for the Development of UIN K.H. Abdurrahman Wahid - Batsnah Nuwaifila (Averroes: Journal for Science and Religious Studies, 2024)
The development of Science and Technology (IPTEK) now universities in Indonesia also adopt technology in education, especially in Islamic education (UIN). This is an interesting thing in this study. Which is a form of Islamization of science that is increasingly growing. The formulation of the problem in this study is “How to actualize the Islamization of Islamic science and science in education for the development of UIN KH. Abdurrahman wahid?". The goal is to develop the Islamization of science and science in education at UIN KH. Abdurahman Wahid Pekalongan. The result of this research is to increase the Islamization of science at UIN KH. Abdurahman Wahid said there was a need for an education system called Inter-disciplinary Sciences in Islam, namely with a new curriculum system in collaboration with other Muslim intellectuals and educators. Simultaneously Muslim intellectuals and educators will reach out to non-Muslim intellectuals and educators, including people of faith, for meaningful dialogue and cooperation.